Application The Multinomial Logistic Regression Method in Analyzing The Relationship Between Local Wisdom to Overcome Stunting - Rahmawati; Amelia; Muliani, Fitra (Program Studi Matematika, Universitas Tadulako, 2024)
Aceh is the region with the highest stunting prevalence rate in 2021. This is in line with (2) that Aceh occupies the third highest position after East Nusa Tenggara (NTT) and West Sulawesi, namely at 24.4%. Meanwhile, Langsa City is one of the districts or cities with a stunting problem above the average tolerance set by WHO. The prevalence of stunting in Langsa City in 2021 was 25.5% and followed in 2022 at 22.1%. For this reason, stunting cases require more intensive handling efforts. The incidence of stunting can be overcome by providing assistance to families regarding nutritional knowledge. This can be done on an ongoing basis starting from pregnant women, breastfeeding mothers, and assistance for mothers or families who have babies aged 2 to 5 years. This assistance is provided with the aim of being able to anticipate as early as possible the factors that cause stunting, one of which is social and cultural. The results of the research show that from the model formed, it shows that the variables nutritional status and maternal education have a significant effect on stunting with a sig value < 0.05 and local wisdom, namely Meugang and Mee Bu tujoh, has a relationship with the incidence of stunting, namely, with a sig value < 0 .05.